The Poultry Industry through the Experts’ Eyes - Lendvai, Edina (Acta Agraria Debreceniensis, 2004)
In my study reveal the situation of the poultry industry. In my research, I used the regularly adopted qualitative method, i.e. the interview. I conversed with the managers of the most important poultry factories, and asked them about the position of the Hungarian poultry sector, the possibility of improving its position, the changes in consumer behaviour, in marketing strategies, means and methods.The managers talked about the necessity of collaborating between factories. They agreed on the dominance of commercial chains. In their opinion, these prejudice their chances. They emphasized about the increasing role of processed products and the growing number of sell-stimulated marketing means. The consumer behaviour has changed in the last 10 years too, which helps the market of processed poultry products.